2001
DOI: 10.1002/em.1021
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous mutation of the lacI transgene in rodents: Absence of species, strain, and insertion‐site influence

Abstract: Comparison of spontaneous mutation spectra derived from different transgenic constructs can provide valuable insights for interpreting the mechanisms of spontaneous mutation. In this study, spontaneous mutation frequencies and spectra of the lacI transgene are compared in the liver of C57BL/6, B6C3F1, and BC-1 mice and F344 rats. Before correction for clonal expansion, the mutant frequency varied from 2.6 +/- 0.45 to 5.0 +/- 2.4 x 10(-5). Correction for potential clonal expansion reduced the range in mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
3
18
0
Order By: Relevance
“…The remainder of the mutation spectrum was comprised primarily of A:T to G:C transitions (11%); various transversions (7%), with G:C to T:A being the most frequent; and +1/71 insertions/deletions (7%), with 71 deletions being the most common. Interestingly, G:C to T:A, and 71, are also the most frequent transversions, and insertions/deletions, respectively, that are seen in MMR-proficient lacI transgenic rodents (Zhang et al, 2001).…”
Section: Mutation Spectramentioning
confidence: 99%
“…The remainder of the mutation spectrum was comprised primarily of A:T to G:C transitions (11%); various transversions (7%), with G:C to T:A being the most frequent; and +1/71 insertions/deletions (7%), with 71 deletions being the most common. Interestingly, G:C to T:A, and 71, are also the most frequent transversions, and insertions/deletions, respectively, that are seen in MMR-proficient lacI transgenic rodents (Zhang et al, 2001).…”
Section: Mutation Spectramentioning
confidence: 99%
“…The only way to address this problem is to systematically collect and analyze mutation spectra for the same mutational target under different experimental conditions. This approach has been undertaken for lacI and supF (see [8,18,81,155]). …”
Section: Global Factorsmentioning
confidence: 99%
“…43) In sequence analysis of the gpt gene recovered from gpt delta rats, we should note that an unexpected A:T to T:A transversions at position 299 (e.g. nucleotide 299 from the first codon of ATG, in the gpt sequence) was frequently observed.…”
Section: Gpt Assay (6-tg Selection) For Point Mutationsmentioning
confidence: 95%
“…Although lower spontaneous gpt MFs than Muta mouse and Big Blue mouse are observed, the characteristic mutation spectra are similar, and the similarity of spontaneous mutation spectra in different tissues and different rodent strains are also observed with the lacI transgene. 42,43) De Boer et al reported the spontaneous lacI mutations for liver, spleen, bladder, stomach, kidney, bone marrow, lung and skin of Big Blue mice. They showed the similarity of the lacI mutational spectra in all tissues.…”
Section: Gpt Assay (6-tg Selection) For Point Mutationsmentioning
confidence: 99%